Immunomagnetic detection of micrometastatic cells in bone marrow of uveal melanoma patients: a paradox. (February 2015) - Eide, Nils; Faye, Ragnar S.; Høifødt, Hanne K.; Sandstad, Berit; Qvale, Geir; Faber, Rowan; Jebsen, Peter; Kvalheim, Gunnar; Fodstad, Øystein
Abstract Purpose Our objective was to study survival rates with the bone marrow (BM) results in a cohort of uveal melanoma patients with long follow‐up. Methods Mononuclear cell fractions isolated from BM were examined for tumour cells using our immunomagnetic separation (IMS) method. The patients were classified as BM positive or BM negative. Clinical follow‐up, histopathological findings, vital status and cause of death were registered. Results The study included 328 consecutive patients with uveal melanoma from 1997 to 2006. Tumour cells were found in BM samples in 29% (95% CI, 25–34) at enrolment (96 cases). After a minimum follow‐up time of 6 years, 156 (48%) (95% CI, 42–53) melanoma patients had died. The causes were as follows: melanoma metastases 92 (59%), another cancer 20 (13%) and non‐cancer 44 (28%). Nine patients were still living with melanoma metastases. Until the latest work‐up, 101(31%) (95% CI, 26–36) patients had developed melanoma metastases. Cyto‐ or histopathological verification of the metastatic lesions was obtained in 85 cases (84%). In the group with melanoma metastases, 28 tested BM positive at study entry (28%) (95% CI, 19–38). In total, 39 of 101 with metastases tested positive at least once after a maximum of three tests (39%) (95% CI, 29–49). The overall median survival from the first BM test was shorter for the BM negative patients (9.5 years) compared with the BM positive (14.4 years), p = 0.02, log rank test. Conclusion Ocular melanoma cells detected in BM seem to have a positive prognostic impact on survival in contrast to our original hypothesis.